On difficulty, and other essays - Steiner, George, 1929-2020 (Oxford : Oxford university press, 1978)
Text and context.--On difficulty.--Language and psychoanalysis.--The distribution of discourse.--Eros and idiom.--Whorf, Chomsky, and the student of literature.--Dante now.--After the book?
A distinguished collection of essays on language, literature, and philosophy from acclaimed scholar and critic George Steiner On Difficulty is as provocative and relevant today as when its essays were first published. Ranging from critical topics such as the understanding of language to the meaning of meaning, inward speech to the relationship between erotic sensibility and linguistic convention, these eight essays posit myriad topics for exploration and dialogue. George Steiner deals with considerations that are simultaneously literary and philosophical, exploring themes of linguistic privacy.
Keywords: Discourse analysis; Philology, Modern; Psycholinguistics